2018
DOI: 10.1186/s40168-018-0589-y
|View full text |Cite
|
Sign up to set email alerts
|

Specialisation events of fungal metacommunities exposed to a persistent organic pollutant are suggestive of augmented pathogenic potential

Abstract: BackgroundThe impacts of man-made chemicals, in particular of persistent organic pollutants, are multifactorial as they may affect the integrity of ecosystems, alter biodiversity and have undesirable effects on many organisms. We have previously demonstrated that the belowground mycobiota of forest soils acts as a buffer against the biocide pollutant pentachlorophenol. However, the trade-offs made by mycobiota to mitigate this pollutant remain cryptic.ResultsHerein, we demonstrate using a culture-dependent app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 44 publications
5
23
0
Order By: Relevance
“…Detected levels of PAHs were associated with changes in abundances of microbial genes encoding various metabolic functions (Fig. 6d), consistent with a recent study demonstrating alterations in the proteome of soil microbiota following pollutant exposure [50]. Interestingly, genes involved in the metabolism of amino acids and vitamins, which may be important in the maintenance of healthy scalps [33], showed negative correlations with exposure levels of some PAHs.…”
Section: Discussionsupporting
confidence: 90%
“…Detected levels of PAHs were associated with changes in abundances of microbial genes encoding various metabolic functions (Fig. 6d), consistent with a recent study demonstrating alterations in the proteome of soil microbiota following pollutant exposure [50]. Interestingly, genes involved in the metabolism of amino acids and vitamins, which may be important in the maintenance of healthy scalps [33], showed negative correlations with exposure levels of some PAHs.…”
Section: Discussionsupporting
confidence: 90%
“…In addition, a link between catabolism of hydrocarbons and fungal virulence, suggested for human fungal pathogens [ 43 ], was demonstrated in plant pathogenic fungi. For instance, Martins et al [ 44 ] reported an increase in the pathogenic potential in human of some fungi upon exposure to aromatic chlorinated compounds. In plants, Sclerotinia sclerotiorum metabolizes salicylate, a key antifungal defense component of the host [ 45 ] and the virulence of Botrytis cinerea on grape is correlated at least in part with its ability to metabolize stilbene-type phytoalexins [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…Adaptation of Scedosporium species to extreme environments, as well as their thermotolerance and their melanized spores, may predispose these fungi toward pathogenesis favoring their survival in growth factor and nutrient-limited microenvironment encountered in the host tissues. Recently, it was demonstrated that the exposure to an aromatic chlorinated compound and its degradation induce an increased pathogenic potential of fungal communities, which in turn may increase the dispersal of airborne opportunistic pathogens (Martins et al, 2018). As already mentioned, a link between pathogeny and degradation of aromatic compounds has been suggested, but regarding fungi, it was actually demonstrated only for phytopathogenic ones.…”
Section: Discussionmentioning
confidence: 99%